Strategic integration of the enterprises: conceptual model based on knowledge of the personnel - Voronkov, D.; Grynyov, A. (Економічний вісник Донбасу, 2010)
In the article problems of formation and development of the human capital as a key factor of solution of enterprise’s tasks are described. The theory of interested parties is considered. The description of the complicated model of interested parties is presented. The strategic integration model of the enterprise on the basis of knowledge transfer is developed and described Key words: knowledge, cooperative-integrated strategy, development, changes, management, strategic management, transformation. У статті описані проблеми формування і розвитку людського капіталу як ключового чинника вирішення складних завдань на підприємстві. Розглянута теорія зацікавлених сторін. Представлений опис ускладненої моделі зацікавлених сторін. Розроблена і описана стратегічна інтеграційна модель підприємства на основі трансферту знань. Ключові слова: знання, коопераційно-інтегрована стратегія, розвиток, зміни, менеджмент, стратегічний менеджмент, трансформація. В статье описаны проблемы формирования и развития человеческого капитала как ключевого фактора решения сложных задач на предприятии. Рассмотрена теория заинтересованных сторон. Представлено описание усложненной модели заинтересованных сторон. Разработана и описана стратегическая интеграционная модель предприятия на основе трансферта знаний. Ключевые слова: знания, кооперационно-интегрированная стратегия, развитие, изменения, менеджмент, стратегический менеджмент, трансформация.